A content analysis of teaching approaches in the Basic English for Young Learners textbook - Nisrina, Nisrina; Avianta, Rindu; Shafira, Nur Alya; Rahayu, Sri (Universitas Merdeka Malang, 2025)
This study conducts a content analysis of teaching approaches embedded in the Basic English for Young Learners textbook. Using a qualitative checklist-based analysis, the study examines how instructional methods are represented through the book’s grammar explanations, exercises, and learning activities, with particular attention to the presence of traditional and contemporary English language teaching approaches. The findings indicate that the Grammar Translation Method (GTM) is the primary approach utilized in the book. The content emphasizes grammar rules, vocabulary acquisition, and sentence translation from English to Indonesian. While the book provides various written exercises, it lacks components that promote speaking, listening, and interactive communication. Furthermore, the study reveals the absence of Communicative Language Teaching, Text-Based Learning, and Digital Learning approaches. These limitations suggest that the book focuses mainly on structural aspects of language learning rather than communicative competence. Despite its usefulness in helping beginners understand grammatical concepts, the textbook would be more effective if combined with modern, student-centered approaches that enhance all language skills. The results of this study are expected to provide valuable insights for English teachers and curriculum developers in selecting and designing an English textbook for young learners.